eSurMent: An Educational Institution Services Customer Satisfaction Measurement (CSM) Mobile Application Evaluation Tool using Opinion Mining with Sentiment Analysis - Anthony, John Edgar; Asni Tafrikhatin; Ari Waluyo (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
The sentiment is the action or point of view of a person based on experience. Evaluation for Offices is one way of getting emotions or feedbacks from clients. A person's response serves as an assessment of the quality of higher education standards. For the administrators to gather feedback from the clients/customers regarding their satisfaction or performance inside the offices or department premise, eSurMent was used as a gathering data tool. The study identifies the strengths and weaknesses of Educational Institution Services based on users' positive and negative responses. It provides a sentiment score from the qualitative data and a numerical response rating from the quantitative evaluation data, and a description of the evaluation results from users. Sentiment analysis is one way of surveys and polls to analyze the responses that researchers found to determine positive and negative reactions from students. Therefore, school administrators will be more aware of the shortcomings of users. Reports generated by the system can be used for self-improvement in the institution. In addition, the results of job evaluations can be used as the basis for opportunities, achievements, or marketing strategies.